Pengembangan bahan ajar modul berbasis flipbook pada mata peajaran komputer akuntansi transaksi perusahaan dagang guna mendukung proses pembelajaran peserta didik XII AKL 1 di SMKN 1 Jombang - Yusi Nisfu Syabana; Joni Susilowibowo (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
Development research, whose purpose is to form new products. This research model in the form of 4D development includes Define, Design, Develope, and Disseminate by Thiagarajan, Dorothy S.Semmel &Melvyn I. Sommel. But at the dissemination stage (Dissemination) researchers have limited capabilities when carrying out the spread. Due to time and cost constraints. The subjects of this study include linguists, material experts, and graphicists with the type of method chosen is qualitative and quantitative. Quantitative data in the form of validity sheets that have been scored by validators in the form of percentages and qualitative data in the form of notes based on the product study of the study that is then described for improvement. Research instruments in the form of open and closed questionnaires containing research sheets and validity test sheets from material experts, linguistics, graffiti, and validators. And compiled based on the feasibility of teaching materials by BSNP (2014). Based on the study sheet produces analysis with qualitative descriptive while validation sheet produces analysis with quantitative descriptive. Techniques for data analysis are qualitative and quantitative. Descriptiveikualitative contains analysis sheets to study the stuffing of suggestions and criticisms from expert lecturers as a completeer of flipbook-based modules that have been developed. While descriptive quantitative contains validity sheets from experts. The main purpose of this study is to analyze how the development process and feasibility in this development researchers concluded that the development of flipbook-based module teaching materials in computer subjects accounting transactions of trading companies is declared feasible because it obtained 86%.